Growth of functional cranial components in rats submitted to intergenerational undernutrition - Cesani Rossi, María Florencia (2006)
The aim of the present study was to discover how intergenerational undernutrition affects the growth of major and minor functional cranial components in two generations of rats. Control animals constituted the parental generation (P). The undernourished generations (F1 and F2) were fed 75% of the control diet. Animals were X-rayed every 10.days from 20 to 100 days of age. The length, width and height of the major (neurocranium and splanchnocranium) and minor (anterior-neural, middle-neural, posterior-neural, otic, respiratory, masticatory and alveolar) cranial components were measured on each radiograph. Volumetric indices were calculated to estimate size variations of these components. Data were processed using the Kruskal-Wallis and Kolmogorov-Smirnov tests for two samples. Impairment in splanchnocranial and neurocranial growth was found, the latter being more affected than the former in F1. Comparison between F2 and F1 animals showed cumulative effects of undernutrition in both major and minor components (anterior-neural, respiratory, masticatory and alveolar in males, and middle-neural and respiratory in females). Such differential effects on minor components may reflect a residual mechanical strain resulting from the linkage between components. This phenomenon was clearly observed in the neurocranium and could be understood as an adaptive response to the demands of the associated functional matrices. © 2006 The Authors Journal compilation © 2006 Anatomical Society of Great Britain and Ireland.